Navigating Big Data Ethics: An Analysis Through Al-Attas's Islamic Worldview - Julian Azma, Aldin; tazkiyah, saffana Lam’a; Abdurrahman, Muhammad Yahya (Journal Of Middle East and Islamic Studies, 2024)
The term "Big Data" is used to describe a collection of data that is both vast in scale and highly complex, and which is expected to continue growing in size. The indication of a secular collection, processing, and use of big data makes it imperative to consider big data from a moral responsibility and ethical perspective. This article seeks to integrate Islamic values and principles from the perspective of Syed Naquib Al Attas, with a particular focus on ethics and morals in the context of big data. This research employs a literature review methodology with a descriptive-analytical approach, Al Attas works, and related issues. The outcome of this research is an understanding of Al Attas' perspective on Islamic thought and its implications for big data. The ideas of human nature (fitrah), manners (adab), knowledge and wisdom (‘ilm and hikmah), as well as the Islamization of knowledge, can serve as a reference point for emphasizing the importance of ethics and morals in the collection, access, and processing of Big Data. This approach can ensure the relevance of Al Attas' views and help prevent the misuse of Big Data.